The Role of Growth Hormone in Depression: A Human Model - Algahtany, Mubarak; Sharma, Shubham; Fahoum, Khalid; Jing, Rowan; Zhang, Stanley; Kovacs, Kalman; Rotondo, Fabio; Lee, John; Vanek, Irene; Cusimano, Michael D. (Frontiers in Neuroscience, 2021)
Background: Although the relationship between acromegaly and depression has been ascribed to the effects of chronic disease, the role of growth hormone (GH) and insulin like growth factor-1 (IGF-1) is not clear. Objective: To determine whether related hormones levels in acromegalics are correlated with depressive symptoms and whether these symptoms are ameliorated following surgery. Methods: A prospective cohort study was conducted on patients diagnosed with acromegaly (n=15) or non-functioning pituitary adenomas (NFPA; n= 20, as controls) and undergoing first-time surgery, who completed the Center for Epidemiological Studies Depression (CES-D) questionnaire both pre-surgery and post-surgery. The primary outcome was the patient’s severity of depression symptomatology using the CES-D score; GH, IGF-1 levels, and tumor characteristics were also measured. Results: Hormone levels (GH and IGF-1) and depression scores in acromegaly patients showed significant reductions following surgery (p<0.05). The average change in CES-D score was 5.73±2.58 (mean ± SE). A moderate correlation was found between GH levels and CES-D scores (r = 0.52, p<0.01). The depressed affect subscale accounted for the most improvement in CES-D scores postoperatively and correlated most highly with GH levels. We did not find similar declines in the matched cohort of NFPA patients. Conclusions and Relevance: Surgical resection of the pituitary tumor in acromegaly patients leads to reduction in GH levels that is correlated with reduction in CES-D scores. The results suggest a role for GH in depression and provide a stronger foundation on which to build the hypothesis that GH impacts affect. The study also suggests that hormones should be factored into the matrix that entails the neuro-biological underpinnings of depressive disorders. Future work could explore the mechanisms involved, further brain and neuropeptide interactions, and, novel potential therapeutic targets in depressive and other mental health disorders.